COVID‐19 in hospitalized lung and non‐lung solid organ transplant recipients: A comparative analysis from a multicenter study. Issue 8 (24th July 2021) - Heldman, Madeleine R.; Kates, Olivia S.; Safa, Kassem; Kotton, Camille N.; Georgia, Sarah J.; Steinbrink, Julie M.; Alexander, Barbara D.; Hemmersbach‐Miller, Marion; Blumberg, Emily A.; Crespo, Maria M.; Multani, Ashrit; Lewis, Angelica V.; et al.
Abstract : Lung transplant recipients (LTR) with coronavirus disease 2019 (COVID‐19) may have higher mortality than non‐lung solid organ transplant recipients (SOTR), but direct comparisons are limited. Risk factors for mortality specifically in LTR have not been explored. We performed a multicenter cohort study of adult SOTR with COVID‐19 to compare mortality by 28 days between hospitalized LTR and non‐lung SOTR. Multivariable logistic regression models were used to assess comorbidity‐adjusted mortality among LTR vs. non‐lung SOTR and to determine risk factors for death in LTR. Of 1, 616 SOTR with COVID‐19, 1, 081 (66%) were hospitalized including 120/159 (75%) LTR and 961/1457 (66%) non‐lung SOTR ( p = .02). Mortality was higher among LTR compared to non‐lung SOTR (24% vs. 16%, respectively, p = .032), and lung transplant was independently associated with death after adjusting for age and comorbidities (aOR 1.7, 95% CI 1.0–2.6, p = .04). Among LTR, chronic lung allograft dysfunction (aOR 3.3, 95% CI 1.0–11.3, p = .05) was the only independent risk factor for mortality and age >65 years, heart failure and obesity were not independently associated with death. Among SOTR hospitalized for COVID‐19, LTR had higher mortality than non‐lung SOTR. In LTR, chronic allograft dysfunction was independently associated with mortality. Abstract : A large multicenter observational study comparing outcomes of lung and non‐lung solid organ recipients with COVID‐19 shows higher mortality for lung recipients.